Analisis Campur Kode Dalam Kanal Youtube Tirta Pengpengpeng: Kajian Sosiolinguistik - Dinan El Haq Rahimahullah; Izzuddin Musthafa; Ade Nandang (University of Brawijaya, 2025)
This study aims to identify the use of code-mixing by dr. Tirta on his YouTube channel and the factors that influence its occurrence. The research employs a qualitative approach with a descriptive research type, which aims to describe and understand a phenomenon. In collecting the data, the researcher used observation and note-taking techniques. The data source observed consists of three videos from the Tirta PengPengPeng YouTube channel. After the data was collected, the next step was classifying it based on specific questions to align with the context, followed by analysis and presentation in tabular form. From the three videos observed and noted, there were 66 instances of code-mixing identified, consisting of (1) 15 instances in video 1, (2) 14 instances in video 2, and (3) 37 instances in video 3. The causes of code-mixing used by Dr. Tirta as the speaker fall into four categories: (1) the speaker, (2) the interlocutor, (3) the situation, and (4) habit. However, the primary influencing factor is the speaker himself, while the other three are merely supporting factors.